(untitled) (Research, Society and Development, 2022)
Objective: to report the experience and challenges of the multidisciplinary service in a long-stay institution for the elderly during the COVID-19 pandemic in Brazil. Method: This is a descriptive study, of the type of experience report, on the experience and challenges of multidisciplinary service in an LSIE during the COVID-19 pandemic in Brazil. Results: The monitoring of the multidisciplinary service took place between February 2020 and February 2021. During this period there was a reorganization of the care plan, with the implementation of actions to promote and protect the health of the elderly, in addition to greater adherence to processes focused on combating the pandemic, such as isolating suspected cases, restricting visits, collecting exams for monitoring suspected and confirmed cases of COVID-19, between others. The exposure of fears and anxieties of the elderly and the entire multidisciplinary team was evidenced as a consequence of the new organization of the service. Conclusion: the pandemic brings challenges in nursing care for institutionalized elderly, requiring cooperation and an abrupt change in the conduct of the multidisciplinary team.